CORRELATION BETWEEN HISTOLOGICAL FINDINGS AND CYTOLOGICAL FINDINGS AND HPV STATUS IN PATIENTS WITH HSIL - RETROSPECTIVE STUDY - Stanojevic, Verdi; Tofiloska, Valentina; Kostadinova Kunovska, Slavica; Dimitrov, Goran; Mircevska, Megi; Ivkovska, Tamara (Македонско лекарско друштво = Macedonian medical association/De Gruyter, 2025)
Introduction. Cervical intraepithelial neoplasia (CIN) and invasive cervical cancer are most commonly caused by human papillomavirus, which causes malig¬nant transformation of cervical epithelial cells. The aim of this study was to investigate the association between different HPV types and histological changes of the cervix in patients in our hospital. Methods. In the period from January 2022 to Decem¬ber 2023, an analysis of 100 samples was made with histological findings confirmed by biopsy from the University Clinic for Gynecology and Obstetrics in Skopje. The relationship between HRHPV and high-grade CIN and CIS, as well as the age-dependent prevalence of single HPV infection, were examined. Results. In both CIN2, CIN3 and CIS group, HPV16, 18, 31, 33 and 58 were detected as the top 5 high-risk human papillomavirus (hrHPV) types. HPV16 was the predominant genotype in CIN2, CIN3 and CIS, with 44.23%, 60.53% and 90% respectively. The prevalence of HPV16 was most common in all age groups. The peak incidence of CIN2 was observed from 31-40 and 41-50 years (28.85%), and CIN3 from 21-30 (28.95) and 51-60 years (23.68), and CIS from 31-40 (40%) and 41-50 years of age (30%). Conclusion. If circumstances permit, women between the ages of 21 and 60 are advised to undergo norma¬tive screening for high-grade CIN. Patients who test positive for HPV16 should be prioritised for opportu¬nistic screening. Patients infected with other forms of HPV should also be treated seriously if they are ladies 61 years of age or older. The most prevalent genotypes in our patients were HPV16, 18, 31, 33 and 58. Therefore, a vaccine including these dominant genotypes may be crucial for preventing cervical cancer.
КОРЕЛАЦИЈА ПОМЕЃУ ХИСТОЛОШКИТЕ НАОДИ И ЦИТОЛОШКИТЕ НАОДИ И СТАТУСОТ НА ХПВ КАЈ ПАЦИЕНТИ СО ХСИЛ – РЕТРОСПЕКТИВНА СТУДИЈА
Keywords: CIN; HPV; malignant transformation